Victim’s interests and the role of probation officers in victim-offender mediation: Theoretical analysis and the Greek juvenile justice system - Panagos Konstantinos I. (Temida)
The present paper focuses on the role of probation officers for juvenile offenders in victim-offender mediation and on the main challenges for the protection of victims’ interests. The general nature of probation officers’ duties has been characterized as ‘offender-focused’. However, according to the Directive 2012/29/EU, restorative justice includes processes through which the victim and the offender can participate actively in resolving the problems that occur from the offence, with the help of an impartial third party. The Greek juvenile justice system will be examined as a case study. The analysis reveals that the Greek legislator has adopted a ‘quasi-restorative’ practice that promotes juvenile offenders’ rehabilitation and socialization. This fact raises concerns regarding the ‘legitimation’ of mediation process from a victimological perspective. Special emphasis is given to the significance of the informed consent that should be provided by the victims in order to participate in the process based on the procedural justice theory.